IMPACTS OF REPLACING THE AMAZON RAINFOREST WITH PASTURE ON SOIL PROPERTIES - Sandra Cátia Pereira Uchôa; Sasha de Souza Farage; José Maria Arcanjo Alves; Carlos Henrique de Lima Matos; Ingridy do Nascimento Tavares; Valdinar Ferreira Melo (Revista de Agricultura Neotropical)
The conversion of the Amazon rainforest into pasture significantly impacts soil quality, affecting biodiversity, biogeochemical cycles, and carbon stocks. Studies indicate a reduction in microbial activity and biomass associated with this transformation. This study investigated the impact of converting forest into pasture on soil attributes in the northern Amazon, specifically at the Canto Verde farm in Iracema, Roraima, Brazil. Three land use systems were analyzed: Native Forest (NF), Brachiaria brizantha (BB), and Brachiaria humidicola (BH). Soil samples were collected at two depths (0-0.10 m and 0.10-0.20 m) in four representative blocks of 1 ha in each system. Chemical, physical, and biochemical properties, and microbial and metabolic coefficients were analyzed. The results were subjected to analysis of variance and the Tukey test (p<0.05). The transition from NF to agricultural use with Brachiaria significantly altered soil attributes. There was an increase in pH in the BB and BH systems and a reduction in total organic carbon and microbial biomass. Basal respiration and dehydrogenase activity decreased, indicating stress in the transformed systems. The BH system showed higher metabolic quotient (qCO2) and lower microbial quotient (qMIC) values, highlighting the adverse effects of converting forests into pastures on soil microbiological activity. The conversion of forests into pastures negatively affects the soil, requiring sustainable agricultural practices.